The segmentation pattern of bronchial tree and its anatomical variations. A bronchoscopy study - Adhikari, Mahesh Mani; Thakur, Binay (Nepalese Journal of Cancer, 2025)
Background: Advances in thoracic surgery and respiratory medicine has shown the rising importance of bronchoscopy. This study aimed to describe the prevalence of different bronchial anatomic branching patterns observed during bronchoscopy. Methods: A total of 104 patients underwent bronchoscopic evaluation for various indications, mostly as a part of malignancy workup. Segmental as well as subsegmental bronchi were properly identified. Data was entered and analyzed using IBM SPSS v25. Results: Various types branching patterns were observed, namely in right upper lobe(RUL) (four types), right lower lobe(RLL) (six types), upper division of left upper lobe (LUL) (two types) and left lower lobe (LLL) ( three types). Presence of Subsuperior(B*) bronchus was noted in 35.8% cases. Conclusion: Segmental variations of various patterns are not uncommon and improved knowledge of these anatomical variations are important to plan intervention like segmentectomy. Bronchoscopy plays an important role in identifying different segmental variations.